Phyllonorycter malellus (Gerasimov) leaf-miner of Pomoideae and Prunoideae in Italy (Lepidoptera Gracillariidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Morphological and biological notes on Phyllonorycter malellus (Gerasimov), leaf-miner living on Malus spp. and other Rosaceae in Italy, are reported.
Keywords: Phyllonorycter malellus; leaf-miner; Rosaceae; orchards; Italy